The Use of Films as an Educational Medium in Learning Civic Education as a Preventive Effort Against Moral Decradation in The Age Of 4.0 - Rahmayanti, Esty (Capture : Jurnal Seni Media Rekam, 2023)
Moral degradation in elementary schools (SD) is increasingly worrying. This can be seen from the many deviations in behavior by elementary school students, such as fights between students, rape, bullying, drugs, sexual harassment, and smoking in the school environment. Moral education in Citizenship Education (PKn) learning is an effort to overcome moral degradation for students. This research aims to describe the implementation and benefits of learning using film teaching media as an effort to prevent moral degradation in the 4.0 era. This research is descriptive research with a qualitative approach. The data analysis used is interactive analysis including data collection, data reduction, presentation and conclusions. The result of this research is that the implementation of civics learning using film teaching media at Gedongkiwo State Elementary School has inspired students to live up to the moral values ​​contained in the Laskar Pelangi film, such as the spirit of studying, responsibility, honesty, hard work, creativity, independence, love of the country, and social care, while the benefits of learning using film teaching media can improve the quality of learning to make it more enjoyable. Young citizens in the 4.0 era, apart from being required to master technology, must also have good morals, so that moral degradation in the 4.0 era can be prevented from an early age. From the data, it is recommended that teachers use film teaching media in civics learning in elementary schools to improve the quality of learning. Keywords: film, citizenship education, moral degradation.